2020
DOI: 10.1126/sciadv.abb8471
|View full text |Cite
|
Sign up to set email alerts
|

YAP-mediated mechanotransduction tunes the macrophage inflammatory response

Abstract: Macrophages are innate immune cells that adhere to the extracellular matrix within tissues. However, how matrix properties regulate their function remains poorly understood. Here, we report that the adhesive microenvironment tunes the macrophage inflammatory response through the transcriptional coactivator YAP. We find that adhesion to soft hydrogels reduces inflammation when compared to adhesion on stiff materials and is associated with reduced YAP expression and nuclear localization. Substrate stiffness and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
170
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(193 citation statements)
references
References 47 publications
9
170
0
Order By: Relevance
“…It has been reported that soft implant materials reduce expression of inflammatory markers in surrounding macrophages when compared to stiff materials [44] and ADSCs may play an important role in immunomodulation by secreting paracrine signals [45].…”
Section: Delivery Of Adscs Via the Caneu Hydrogel Results In The Suppression Of Apoptosis And Inflammation In Sci Through The Promotion Omentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that soft implant materials reduce expression of inflammatory markers in surrounding macrophages when compared to stiff materials [44] and ADSCs may play an important role in immunomodulation by secreting paracrine signals [45].…”
Section: Delivery Of Adscs Via the Caneu Hydrogel Results In The Suppression Of Apoptosis And Inflammation In Sci Through The Promotion Omentioning
confidence: 99%
“…Meli et al [44] reported that a soft hydrogel matrix enhanced adhesion and suppressed the M1 polarization of macrophages. Previous studies have also demonstrated the immunomodulatory potential of ADSCs via paracrine signals, including growth factors, cytokines, and exosomes [45].…”
Section: Discussionmentioning
confidence: 99%
“…Almost all cellular signals that have YAP as a main downstream target effector (i.e., mechanotransduction, Rho GTPase, Wnt signaling, inflammation and metabolic variation [ 77 , 81 , 85 , 86 , 87 , 88 , 89 , 90 ]) ( Figure 3 ) are highly involved in the regulation of tissue repair, and by referring to cancers as “wounds that do not heal”, the prominent involvement of YAP in the regulation of tumor growth appears logical [ 91 ]. Accordingly, sustained cell proliferation is among the best characterized YAP-driven biological responses, emphasizing its remarkable involvement in tissue development by directly acting on the amplification of progenitor cells.…”
Section: Yap-dependent Signaling Pathways Impacting Cancermentioning
confidence: 99%
“…Future studies should consider tailoring physical features of scaffolds (e.g., stiffness, topography, mechanical stability, and degradation profiles) that compensate dynamic mechanical alterations of injured tissues. There is emerging evidence that physical cues applied to injured tissues are critical to regulate tissue repair and even immune responses via mechanotransduction ( 94 - 97 ). However, their roles in 3D spheroids have not been fully investigated yet.…”
Section: Future Directionsmentioning
confidence: 99%